Polysomnography and Nocturia Evaluations after Uvulopalatopharyngoplasty for Obstructive Sleep Apnea Syndrome - Tsou, Yung-An (J Clin Med, 2020)
A higher incidence rate of nocturia in patients with obstructive sleep apnea (OSA) has been observed. We investigated the differences in clinical examinations between OSA patients with and without nocturia, and further compared those with successful and unsuccessful uvulopalatopharyngoplasty (UPPP). This retrospective study enrolled 103 patients with OSA undergoing UPPP. Patients were diagnosed with OSA by following the 2018 American Academy of Sleep Medicine (AASM) Scoring Manual Version 2.5. Patients were divided into two groups depending on if they urinated more than twice per night. The medical data of body mass index (BMI), nocturia frequency per night, apnea–hypopnea index (AHI), Epworth Sleepiness Scale (ESS), International Prostatic Symptom Score (IPSS), and Overactive Bladder Symptom Score (OABSS) were analyzed before and after uvulopalatopharyngoplasty (UPPP) surgery. All of the measurements were compared between successful and unsuccessful surgery in the non-nocturia or nocturia groups, respectively. Fifty patients (41 males and nine females) without nocturia were assigned to group 1, and 53 patients (43 males and 10 females) with nocturia were assigned to group 2. Nocturia frequency and post-surgery AHI in group 2 were significantly higher than those in group 1 (p < 0.05). Significant decreases in IPSS and OABSS were observed in the successful surgery subgroup of group 2 (p < 0.05). A significant decrease in post-surgery AHI was observed between unsuccessful and successful surgery in patients with nocturia (p < 0.05), but not in the non-nocturia group (p > 0.05). Although AHI had a significant correlation to nocturia frequency in all OSA patients before UPPP, no significant correlation between AHI reduction and nocturia frequency was found. UPPP appeared to be an effective treatment for nocturia associated with OSA. OSA should be taken into consideration for patients who complain of nocturia syndrome. The relationship of AHI reduction and nocturia improvement after OSA treatment with UPPP is still unclear. In addition, it is necessary to establish the existence of nocturia in patients with OSA, as a result of its high prevalence in OSA patients. UPPP could reduce the symptoms of OSA and could also contribute to a reduction of nocturia even in the unsuccessful surgery group.